Assessment Clinical Association of Thyroid Function in Women of Reproductive Age Group with Abnormal Uterine Bleeding - Rabia Chaudhary, Komal Aftab, Ghazala Iqbal, Summaiya Moazzam, MS. Khushboo Chandio, Tania Naveel, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Abnormal Uterine Bleeding occurs when the frequency and quantity of menstrual bleeding in females is significantly altered. It is the most prevalent clinical presentation in gynecology, affecting more than 20% of the female population, and is characterized by variations from normal menstruation in terms of irregularity in periods, frequency, duration of blood flow, amount of blood loss, and cyclicity. Thyroid hormones had significant effects on the female reproductive system, such as delayed puberty, infertility, premature menopause, recurrent abortions, and AUB. The AUB is significantly associated with thyroid secretions, and any patient who complains of AUB or irregular menstruation must have thyrotoxicosis ruled out. Objectives: This study was conducted at the Department of Obstetrics and Gynecology, Nishtar Hospital, Multan, Pakistan, (2021-22) in order to evaluate the clinical association between thyroid function and AUB in women of different reproductive age groups. Methods: This cross-sectional study was conducted in the outpatient department of Obstetrics & Gynecology, Nishtar Hospital, Multan, from 1st December 2021 to 31st May 2022. 320 patients participated in the study and were examined clinic-pathologically and were allocated into three groups based on their thyroid profile (euthyroid, hyperthyroid and hypothyroid, respectively) and further predisposition risk factors were recorded and analyzed. Results: It was discovered that extreme age groups of adolescence and pre-menopause phase significantly (p<0.05) increased the incidence of AUB. The incidence of AUB was also elevated (p<0.05) among patients with an abnormal BMI, women with multiple pregnancies, and married women. The menstrual bleeding pattern was also studied in females, with polymenorrhea (131/320) being the most prevalent (p<0.05), followed by menorrhagia (79/320), metrorrhagia (59/320), oligomenorrhea (42/320), and amenorrhea (9/320) having a significantly lower incidence (p<0.05). The incidence rate of thyroid disorders was 28.12% (90/320), with hypothyroidism affecting 77(24.06%) and hyperthyroidism affecting 13(4.06%) patients (p<0.05). Practical implication: AUB is significantly associated (p<0.05) with thyroid hormones, therefore for early diagnosis of the underlying etiology and treatment of the patients by preventing hysterectomy and other serious surgical interventions, all patients presenting to OPD clinics with the complaint of AUB or irregular menstruation must be ruled out for a thyroid profile in the first instance. Conclusion: It was concluded that thyroid disorders directly affected the BMI, fertility and menstrual cycle of gynecology patients and increased the incidence of AUB along with the medical and gynecological complications. Keywords: Amenorrhea; Hyperthyroidism; Hypothyroidism; Polymenorrhea; Thyrotoxicosis.